Parents’ Perception of and Willingness for Using Internet Based Mental Health Application for Children - Thanh Nam, Tran; Hien, Hoang Thi Thu (VNU Journal of Science: Education Research; Vol 35 No 4, 2019)
Though the trend of using mobile applications in evaluating, supporting mental health issues is becoming more and more popular in the world, it has not been studied in Vietnam. This paper aims to (1) discuss the current situation of using internet based mental health applications from previous studies as well as the effectiveness of these applications; and (2) investigate parents' perceptions of and willingness for using mental health applications for their children as well as obstacles against them. A survey was conducted on 123 high school children’s parents who were recruited from a school in Long Bien district, Hanoi, Vietnam. The literature review results show that mental health software applications in the Internet have been used in many countries around the world and have initially proved their advantages in finance, accessibility and are more effective than traditional interventions in some mental health problems. The quantitative results indicate that parents' understanding of online counseling is limited. After experiencing the functionality of some apps, parents are more willing to let their children use the apps (except for serious issues like self-harm, suicide, addiction or law violation); tend to be more available to the features of the apps when they automatically send assessment information, course information or connect parents and experts to support children. Although ready to let their children use the apps, a number of parents are concerned about the confidentiality of the information, the legality and effectiveness of the apps. Some technologically incapable parents are reluctant to use the apps, worried about online payment risk which may not be covered by the insurance. Some recommendations and limitations of the study are also given.